2002
DOI: 10.1042/bj20020039
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and backbone dynamics of human epidermal-type fatty acid-binding protein (E-FABP)

Abstract: Human epidermal-type fatty acid-binding protein (E-FABP) belongs to a family of intracellular 14-15 kDa lipid-binding proteins, whose functions have been associated with fatty acid signalling, cell growth, regulation and differentiation. As a contribution to understanding the structure-function relationship, we report in the present study features of its solution structure and backbone dynamics determined by NMR spectroscopy. Applying multi-dimensional high-resolution NMR techniques on unlabelled and 15N-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 61 publications
(70 reference statements)
6
45
0
6
Order By: Relevance
“…Previous studies with various i-LBPs have revealed a correlation between ligand-binding affi nity and overall structural stability for several members of this protein family ( 21,36 ). In order to determine whether such a correlation also applies to the cellular retinol carriers, we have now nearly identical to those at pH 6.0 (differences р 0.02 ppm), as shown in Table 2 .…”
Section: Structural Stability Mapping Of Crbp-i and Crbp-ii Based On mentioning
confidence: 55%
See 2 more Smart Citations
“…Previous studies with various i-LBPs have revealed a correlation between ligand-binding affi nity and overall structural stability for several members of this protein family ( 21,36 ). In order to determine whether such a correlation also applies to the cellular retinol carriers, we have now nearly identical to those at pH 6.0 (differences р 0.02 ppm), as shown in Table 2 .…”
Section: Structural Stability Mapping Of Crbp-i and Crbp-ii Based On mentioning
confidence: 55%
“…A critical factor for the structural stability of i-LBPs is a cluster of structural water molecules inside the binding cavity, which developed during the course of an evolutionary specialization of this protein family ( 23 ). These water molecules form an intricate network of hydrogen bonds among each other and with several side chains in the protein interior, thereby strengthening the overall protein structure as previously demonstrated by H/D exchange experiments performed with other i-LBPs ( 21 ).…”
Section: Sequence Comparison Between Crbp-i and Crbp-ii: A Key To Undmentioning
confidence: 79%
See 1 more Smart Citation
“…Three-dimensional structures of these different FABPs have been extensively studied and found to be highly conserved, although their sequence similarities could vary between 20 and 70%. These proteins adopt a mixed ␣-␤ structure, with a typical ␤ barrel made up of 10 antiparallel ␤ strands and covered with a pair of ␣ helices at one end (15)(16)(17).…”
mentioning
confidence: 99%
“…It was proposed that they play a role in cellular lipid uptake and transport, metabolic pathway, and regulation of protein metabolism. Downregulation of E-FABP in has been reported for ESCC [46].…”
Section: Differentiationmentioning
confidence: 91%